PENGARUH PANAS HEATER TERHADAP MESIN PEMBUAT EKSTRUDER FILAMEN 3D PRINTER - Muthi, Hamdan Abdillah; -, Yurika (Jurnal Mahasiswa Terapan; Vol 1 No 4 (2025): Jurnal Mahasiswa Terapan, 2025)
The 3D printing industry is growing rapidly, but the cost of filament materials is still high. The use of plastic filament for 3D printers is a cost-effective and environmentally friendly method. This study focuses on the design of filament ejectors that can control the filament and evaluate the changes in the filament's temperature. The ejectors are heated at various temperatures, such as 162°C, 170°C, and 185°C, to improve filament quality. The analysis shows that thicker filaments can speed up the printing process, but filaments may lose their shape, like in the case of a nozzle. The study aims to improve plastic filament technology and offer solutions for 3D printer materials with lower costs.